Civic Patriotism as Basis for Axiological and Motivational Activity of Personality Involved in Innovative Activity - O B Mikhailova (Peoples' Friendship University of Russia (RUDN University), 2013)
The development of the innovative activity in a personality is impossible without the goals, values and motives of self-fulfillment. This article provides a theoretical analysis and substantiation of the social and psychological role of civic patriotism for the development of the axiological and motivational activity in a personality. It also defines the basic trends of the development of civic patriotism in the contemporary higher education.